Sosialisasi Dan Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Untuk Pengembangan Umkm Jahe Merah Bima Sakti Di Kelurahan Bendo - Devianti, Hidayah Nur Imansari; Budiningsih, Faridhatul Ismah; Ariansyah, Junaidi; Priranti, Yessy Risma; Atasa, Dita; Arum, Dewi Puspa (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
MSME actors in the Bendo Village experience development every year. In this case, MSMEs need a business license to obtain business legality and legal protection from the government. However, business actors in Bendo Village still lack knowledge of the mechanism for making Business Identification Numbers (NIB) through Online Single Submission (OSS). The method used has 3 stages, namely observation and interviews, discussions related to NIB, and implementation of assistance in making NIB. The activity aims to introduce, increase knowledge and assist MSME actors in making NIB.